Effect of dietary Xiao-Chaihu-Decoction on growth performance, immune response, detoxification and intestinal microbiota of pacific white shrimp (Litopenaeus vannamei). Issue 114 (July 2021) - Su, Chen; Liu, Xintian; Lu, Yusong; Pan, Luqing; Zhang, Mengyu
Abstract: Xiao-Chaihu-Decoction (XCHD), a classical traditional Chinese medicine with diverse biological activities, is widely applied to prevent and treat many human diseases. Effects of dietary XCHD on growth performance, immune response, detoxification system, intestinal microbiota and resistance against aflatoxin B1(AFB1 ) of Litopenaeus vannamei was studied. Four isonitrogenous and isolipidic diets were formulated to contain 0, 1, 2, and 5 g/kg (control, XCHD1, XCHD2 and XCHD3) of XCHD, respectively. Seven hundred and eighty shrimp (1.16 ± 0.09 g) were assigned randomly to 12 tanks (400 L, three tanks each group, 65 shrimp in each tank) for 6 weeks. After sampling, 25 shrimp from each tank were selected for a 2-week AFB1 (2500 μg/kg) challenge experiment. The results indicated that the final weight, weight gain and specific growth rate in XCHD2 and XCHD3 groups were significantly increased compared to control. The protease, amylase, superoxide dismutase (SOD), glutathione s-transferase (GST), sulfotransferase (SULT) activities, total antioxidant capacity (T-AOC) and glutathione (GSH) contents in hepatopancreas were significantly increased in XCHD3 groups and the expressions of immune-related genes (Toll, Dorsal and Cru) in hepatopancreas were significantly up-regulated in XCHD2 and XCHD3 groups. High-throughput sequencing analysis revealed that the abundance of Proteobacteria decreased and the abundances of Bacteroidetes increased in XCHD2 and XCHD3 groups. Additionally, AFB1 challenge experiments showed that AFB1 caused histological damage to the hepatopancreas and significantly increased the levels of malondialdehyde (MDA) and protein carbonylation (PC) in hepatopancreas as well as the activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Nevertheless, XCHD could effectively alleviated the growth toxicity, immunosuppression and macromolecular damage caused by AFB1 to shrimp by inhibiting the Phase I enzyme and enhancing Phase II enzyme and antioxidant system. Highlights: Dietary Xiao-Chaihu-Decoction could enhance the growth of Litopenaeus vannamei. Suitable Xiao-Chaihu-Decoction improve the detoxification and immune response of Litopenaeus vannamei. Xiao-Chaihu-Decoction alter the intestinal microbiota of Litopenaeus vannamei. Xiao-Chaihu-Decoction could relieve the toxicity of AFB1 to Litopenaeus vannamei.